Silver fir (Abies alba Mill.) distribution in Slovenian forests - Ficko, Andrej (Zbornik gozdarstva in lesarstva, 2006)
We analysed the characteristics of silver fir (Abies alba Mill.) occurrence and distribution in Slovenia using databases of the Slovenian Forest Service (SFS). Silver fir is the third most widely distributed tree species in Slovenia, occurring in approximately 40 % of total forest area, but abundantly in less than 10 %. Its share in total growing stock varies between separate forest management regions. It is more abundant in the Dinaric and part of the Pre-alpine phytogeographic regions. The highest share in total growing stock reaches at altitudes between 800 m and 1000 m above sea level, forests with silver fir cover the most extensive surface in the altitude belt from 1000 to 1200 m. Silver fir occurs abundantly in 11 syntaxes. Between them, silver fir-beech forests (Abieti-Fagetum dinaricum TREG. 57, syn.: Omphalodo-Fagetum (TREG.57 corr. PUNC.80) MAR et al. 93) strongly prevail, followed by fir forests with fern (Dryopterido-Abietetum KOŠ.65, syn.: Galio rotundifolii-Abietetum BARTSCH.40). Silver fir diameter distribution considerably varies between separate forest management regions. The regions with the highest share of silver fir (Postojna, Kočevje) dominate also in having large diameter silver fir trees, whereas in other regions (e.g. Nazarje, Kranj, Maribor) small diameter silver fir trees are prevalent. Ddevelopmental stage structure shows that in forest stands with silver fir there is a higher share of timber phase, stands in regeneration, youth stands and selective forests. Considering regeneration we can conclude, that more intensive decreasing trend in silver fir share is expected in the Ddinaric phytogeographic region than in northern parts of Slovenia. Successful regeneration due to lower red deer population and balanced stem diameter structure with higher proportion of small diameter trees promise easier conservation of silver fir in northern parts.
Keywords: Abies alba; gozdna vegetacija; gozdni sestoji; jelka; Slovenija